Health surveillance of workers exposed to ionizing radiations in Italy: A review of the Italian Regulation (Legislative Decree no.101/2020) - Francesco CHIRICO; Giuseppe TAINO; Angelo SACCO; Ludovica AZZOLA; Luca SEMBOROWSKI; Nicola MAGNAVITA (GIornale Italiano di Psicologia e Medicina del Lavoro)
In Italy, the practitioner entitled to take clinical responsibility for occupational exposure to ionizing radiations (IRs) is called “medico autorizzato” (MA). In this paper, the authors review the Italian transposition of the EU Directive 2013/59/Euratom of 5 December 2013, namely the Legislative Decree No. 110 released in 2020. This Regulation tries to integrate the medical activity of MA and that carried out by the occupational physicians (called in Italy “medico competente”) appointed in the same company. The Italian Regulation on Radioprotection requires MA to carry out the medical surveillance of exposed workers (category A or B workers). MA must collaborate with the employer in risk assessment and can collaborate to the education of exposed workers through specific training courses. In their review-based protocol, the authors describe, furthermore, the preparation of a health protocol and, after the medical examinations, the participation in the health and safety committee meeting with the employer, the health and safety manager, workers’ representatives, and the MC for discussing on anonymous and collective data for continuous improvement of preventive and protective measures.